Aerosol Jet Printing of Polymer Optical Waveguides - Hamjah, Mohd Khairulamzari; Reitberger, Thomas; Lorenz, Lukas; Franke, Jörg (Springer International Publishing, 2022)
This research presents an advanced fabrication process of aerosol jet printed polymer optical waveguides onto 2D and 3D surfaces. The key advantage of the aerosol printed polymer optical waveguides is the capability of the process to print directly on desired surfaces, which significantly reduced the cost for new/customization production. Comprehensive studies of the optical material selection, printing strategies, printing process optimization and quality characterization of the printed polymer optical waveguide are successfully conducted. With the optimum printing process, the desired aspect ratio of the polymer optical waveguides is obtained at the height to width ratio ofâ€‰ â€‰1:5 and contact angle ofâ€‰ â€‰45° to 60°. Optical analysis of the printed polymer optical waveguide samples record attenuation rates up to 0.2 dB/cm and transmission rates of 10 Gbit/s. These significant achievements are likely to become a game-changer to the existing metallic conductor.
CRIS-Team Scopus Importer:2024-12-16